The Intracellular Immune Receptor Sw-5b Confers Broad-Spectrum Resistance to Tospoviruses through Recognition of a Conserved 21-Amino Acid Viral Effector Epitope. Issue 9 (16th August 2017) - Zhu, Min; Jiang, Lei; Bai, Baohui; Zhao, Wenyang; Chen, Xiaojiao; Li, Jia; Liu, Yong; Chen, Zhengqiang; Wang, Boting; Wang, Chunli; Wu, Qian; Shen, Qianhua; et al.
Abstract : A plant intracellular immune receptor mediates broad-spectrum resistance by recognizing a small conserved PAMP-like region within the pathogen protein. Abstract: Plants use both cell surface-resident pattern recognition receptors (PRRs) and intracellular nucleotide binding leucine-rich repeat (NLR) receptors to detect various pathogens. Plant PRRs typically recognize conserved pathogen-associated molecular patterns (PAMPs) to provide broad-spectrum resistance. By contrast, plant NLRs generally detect pathogen strain-specific effectors and confer race-specific resistance. Here, we demonstrate that the tomato ( Solanum lycopersicum ) NLR Sw-5b confers broad-spectrum resistance against American-type tospoviruses by recognizing a conserved 21-amino acid peptide region within viral movement protein NSm (NSm 21 ). Sw-5b NB-ARC-LRR domains directly associate with NSm 21 in vitro and in planta. Domain swap, site-directed mutagenesis and structure modeling analyses identified four polymorphic sites in the Sw-5b LRR domain that are critical for the recognition of NSm 21 . Furthermore, recognition of NSm 21 by Sw-5b likely disturbs the residues adjacent to R927 in the LRR domain to weaken the intramolecular interaction between LRR and NB-ARC domains, thus translating recognition of NSm 21 into activation of Sw-5b. Natural variation analysis of Sw-5b homologs from wild tomato species of South America revealed that the four polymorphic sites in the Sw-5b LRR domain were positively selected during evolution and are all necessary to confer resistance to tospovirus. The results described here provide a new example of a plant NLR mediating broad-spectrum resistance through recognition of a small conserved PAMP -like region within the pathogen effector.